STRATEGY COASTAL COMMUNITY PANGLIMA RAJA VILLAGE IN SUSTAINABILITY OF LIFE - Rd Siti Sofro Sidiq (Universitas Padjadjaran, 2020)
In general, fishermen or communities in coastal areas are in a state of poverty, underdeveloped in the social and cultural fields, and the quality of human resources is low. This situation occurs because of low education and the lack of functioning of existing business groups. In addition, the fishing profession cannot guarantee the sustainability of daily income as a result of the availability of marine products and unpredictable weather changes. Another aspect that is also of concern is the management and utilization of coastal resources that are not yet optimal. This picture is not much different from the life of the coastal communities in Panglima Raja Village, both physically in the form of environmental degradation and which have an impact on social and economic aspects in the form of family, neighborhood or community problems, as well as other related resources. The research objectives were to 1) find out and study the social and demographic aspects of the coastal community in Panglima Raja Village, 2) to study the livelihood assets of the coastal community of Panglima Raja Village, 3) to study the livelihood strategies of the coastal community of Panglima Raja Village. The research method used is a descriptive case study where data is collected through in-depth interviews, observation, and literature review. The results showed that the social demographics of the Panglima Raja community were heterogeneous with the majority of productive age, lower income and low education level, the community had social, physical, financial, natural and human capital even in limited conditions, while the strategy was is found is a strategy of survival and consolidation without any accumulation strategy.